Static and dynamic deformation response of smart laminated composite plates induced by inclined piezoelectric actuators. (September 2022) - Gohari, Soheil; Mozafari, Farzin; Moslemi, Navid; Mouloodi, Saeed; Alebrahim, Reza; Ahmed, Mizan; Abdi, Behzad; Sudin, Izman; Burvill, Colin
A Levi-type analytical solution procedure is developed to characterize static and dynamic deformation response of smart laminated simply-supported composite rectangular plates induced by inclined piezoelectric actuators under (1) constant electrical voltage and (2) time-dependent electrical voltage with excitation frequency. The key to development of this analytical solution is to employ higher order finite integral transform and discretized higher order partial differential unit step function equations. Unlike earlier studies, this research aims to investigate the effect of inclination angle of piezoelectric actuators on static and dynamic deformation response of laminated composite plates under both static and dynamic conditions. The developed analytical solution procedure is implemented computationally through Matlab-based computer code. Its accuracy is initially investigated through convergence study and results comparison with the published literature for a particular case when inclination angle is θ = 0°, which is only limited to bending deformation response. Since there is no published benchmark data for twisting deformation response analysis caused by inclination angle of piezoelectric actuators (θ ≠ 0°), a set of robust and realistic numerical analysis using Abaqus finite element analysis (FEA) is conducted. Good agreement between the analytical and numerical results is observed. Unlike applied electrical voltage, inclination angle of a piezoelectric actuator does not have a significant impact on twisting deformation response during static mode; whereas, both the excitation frequency and inclination angle can significantly influence maximum amplitude of vibration.